Beyond the encyclopedia: Collective memories in Wikipedia. (January 2014) - Ferron, Michela; Massa, Paolo
Collective memory processes have been studied from many different perspectives. For example, while psychology has investigated collaborative recall in small groups, other research traditions have focused on flashbulb memories or on the cultural processes involved in the formation of collective memories of entire nations. In this article, considering the online encyclopedia Wikipedia as a global memory place, we analyze online commemoration patterns of traumatic events. We extracted 88 articles and talk pages related to traumatic events, and using logistic regression, we analyzed their edit activity comparing it with more than 370, 000 other Wikipedia pages. Results show that the relative amount of edits during anniversaries can significantly distinguish between pages related to traumatic events and other pages. The logistic regression results, together with the transcription of a group of messages exchanged by the users during the anniversaries of the September 11 attacks and the Virginia Tech massacre, suggest that commemoration activities take place in Wikipedia, opening the way to the quantitative study of online collective memory building processes on a large scale.